REACTION BETWEEN SLAB-DERIVED MELTS AND PERIDOTITE IN THE MANTLE WEDGE: EXPERIMENTAL CONSTRAINTS AT 3.8 GPA - Rapp R.P.; Applegate G.S.; Shimizu N.; Norman M.D. (My University, 1999)
Laboratory experiments on natural, hydrous basalts at 1–4 GPa constrain the composition of “unadulterated” partial melts of eclogitized oceanic crust within downgoing lithospheric slabs in subduction zones. We complement the “slab melting” experiments with another set of experiments in which these same “adakite” melts are allowed to infiltrate and react with an overlying layer of peridotite, simulating melt:rock reaction at the slab–mantle wedge interface. In subduction zones, the effects of reaction between slab-derived, adakite melts and peridotitic mantle conceivably range from hybridization of the melt, to modal or cryptic metasomatism of the sub-arc mantle, depending upon the “effective” melt:rock ratio. In experiments at 3.8 GPa, assimilation of either fertile or depleted peridotite by slab melts at a melt:rock ratio ~2:1 produces Mg-rich, high-silica liquids in reactions which form pyrope-rich garnet and low-Mg# orthopyroxene, and fully consume olivine. Analysis of both the pristine and hybridized slab melts for a range of trace elements indicates that, although abundances of most trace elements in the melt increase during assimilation (because melt is consumed), trace element ratios remain relatively constant. In their compositional range, the experimental liquids closely resemble adakite lavas in island-arc and continental margin settings, and adakite veins and melt inclusions in metasomatized peridotite xenoliths from the sub-arc mantle. At slightly lower melt:rock ratios (~1:1), slab melts are fully consumed, along with peridotitic olivine, in modal metasomatic reactions that form sodic amphibole and high-Mg# orthopyroxene.